PROFIL LITERASI SAINS SISWA SMP PADA PEMBELAJARAN IPA TERPADU TEMA PENCEMARAN LINGKUNGAN - Annissa Mawardini; Anna Permanasari; Yayan Sanjaya (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
The purpose of this study was to describe the junior high school students’ scientific literacy profile in integrated science learning on the environmental pollution theme. The subjects were the 7th grade of Junior High School in Bandung city. The method of this study was descriptive. Data was collected using a test of science literacy, attitude scales, performance assessment sheet, questionnaire sheet, and interview format. Integrated science learning using scientific approach. Average scientific literacy for all student was 69%, the attainment of student scientific competence in identifying scientific issues was 77%, in explaining phenomena scientifically was 72%, and in utilizing scientific evidence was 59%. The attainment of student scientific literacy in domain content science was 81% in air pollution and acid rain, 74% in soil pollution, 60% in global warming and 56% in water pollution. The attainment of student’s attitudes toward science in supporting scientific inquiry was very high category, responsibility toward resources and environment and interest in science was high category. The average of performance assessment when doing practicum was 80%, and on practicum report was 65%. Teacher and students responded positively to the integrated science learning and it’s assessment. Keywords: scientific literacy, junior high school student, integrated science learning on the environmental pollution theme